Function and Immunochemistry of Prekallikrein-High Molecular Weight Kininogen Complex in Plasma - Scott, Cheryl F. (1980)
Plasma from individuals with high molecular weight (HMW) kininogen deficiency has been reported to be deficient in prekallikrein as measured by radial immunodiffusion, prekallikrein coagulant activity, and/or kaolin-activated arginine esterase activity. The discovery that prekallikrein and HMW kininogen circulate as a complex in plasma led us to reevaluate the antigenic and functional properties of prekallikrein in HMW kininogen-deficient plasma as well as in normal plasma. The low prekallikrein antigen level in an individual with HMW kininogen deficiency was corrected to the normal range (80-95%) by the addition of 0.2 U/ml of purified HMW kininogen. A similar increase in apparent prekallikrein antigen was observed when purified prekallikrein and HMW kininogen were combined. The correction of the apparent prekallikrein defect in this HMW kininogen-deficient plasma coincided with the formation of a prekallikrein-HMW kininogen complex as demonstrated by immunoelectrophoresis. Similar findings were demonstrated with purified prekallikrein and HMW kininogen by immunoelectrophoresis as well as crossed immunoelectrophoresis. The coagulant activity in HMW kininogen-deficient plasma was increased in a dose-dependent manner by the addition of HMW kininogen, reaching 85% of normal level at a concentration of 0.2 U/ml. Kaolin-activated arginine esterase activity (kallikrein) in HMW kininogen-deficient plasma was fully corrected when HMW kininogen was added to the deficient plasma after depletion of kallikrein inhibitors. The functional and antigenic concentration of prekallikrein in plasma from four other HMW kininogen-deficient individuals was similarly corrected to normal after adding HMW kininogen. Addition of HMW kininogen increased the apparent prekallikrein activity in native normal plasma (as measured by esterase activity) but not in normal plasma in which inhibitors were inactivated. The apparent prekallikrein antigen concentration (as measured by radial immunodiffusion or electroimmunodiffusion) increased upon addition of HMW kininogen. Immunoelectrophoresis as well as gel filtration of normal plasma revealed the presence of free prekallikrein (17-38% of the total) in addition to the HMW kininogen-prekallikrein complex previously reported. This study emphasizes the influence of HMW kininogen on both functional and immunologic determinations of prekallikrein.